Development and Validation of a Robust RP-HPLC Method for Rufinamide Quantification in Pharmaceutical Dosage Forms - Thonta Harini Kumari; Shaik Ejas (Emerging Trends in Personalized Medicines, 2024)
The creation and validation of a simple, precise, and targeted reverse phase high-performance liquid chromatographic (RP-HPLC) approach allowed for the quantification of rufinamide in pharmaceutical dosage forms. With a mobile phase of methanol and water (50:50, v/v), the technique used a gradient mode Symmetry Qualisil gold C18 column (4.6 x 150mm, 5 μm). For the detection method, a flow rate of 1 mL/min was employed at 220 nm. During a 5.203-minute retention period, the primary peak for rufinamide was detected. Linearity, accuracy, precision, robustness, ruggedness, limit of quantitation (LOQ), robustness, and precision were among the criteria that were evaluated during the method's validation. With a correlation value (r) that was almost equal to unity, the method demonstrated good linearity in the concentration range of 10 to 60 mcg/ml. The sensitivity of the method was demonstrated by the determination of the LOD and LOQ for rufinamide, which were found to be 1.51 mcg/mL and 4.60 mcg/mL, respectively. The method's repeatability and reproducibility were demonstrated by precision studies, which showed low relative standard deviation (RSD) values for both intra-day and inter-day analysis. Recovery experiments at three distinct concentration levels, which produced recovery values ranging from 99.08% to 100.93%, validated the accuracy of the procedure. By purposefully altering the experimental settings and chromatographic conditions, the robustness and roughness of the method were assessed, proving its dependability and appropriateness for regular analysis. In summary, the new RP-HPLC method provides a precise, accurate, and dependable way to measure rufinamide in pharmaceutical formulations. Due to its simplicity and specificity, it can be used in pharmaceutical enterprises for routine quality control analyses that guarantee the potency and purity of dosage forms containing rufinamide.
Keywords: Method validation; Pharmaceutical dosage forms; RP-HPLC; Rufinamide; Sensitivity